COMPUTERIZED USE OF MATERIAL IN PROCESS CONTROL PRODUCTION IN PT. RADEMA INDAH SEMESTA - Rudi Novanto; Ir. Aqwam Rosadi Kardian (Jurnal Sistem Informasi, 1997)
To solve the problems arising in the production process, then the proper PT. RademaIndah Semesta in the field of computerized control of the use of materials in theirproduction process.With the smooth running of the computerized production process expected to furtherincrease. Besides, with computerized data storage can save space and can be betterand easier to be seen again. In terms of presentation and THE DATA processing canbe performed quickly and accurately.